2006
DOI: 10.1051/alr:2007003
|View full text |Cite
|
Sign up to set email alerts
|

Diamondvs.square mesh codend in a multi-species trawl fishery of the western Mediterranean: effects on catch composition, yield, size selectivity and discards

Abstract: Selectivity studies usually describe the effects on target species, whereas information on by-catch and discards is scarce. Nevertheless, large quantities of undersized individuals and invertebrates are discarded in the Mediterranean multi-species bottom trawl fishery. The present work analyses the data from two surveys carried out on the shallow and deep continental shelf (50-78 m, and 147-189 m, respectively) off the Balearic Islands (western Mediterranean). In these surveys, the traditionally used 40 mm dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
76
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 19 publications
15
76
2
Order By: Relevance
“…Given that the focus of the Queensland mesh trials was to reduce by-catch by using square mesh, alternative square-mesh sizes were not tested; however, our study showed that largersized square-mesh codends than those tested in Queensland have the potential to concurrently reduce by-catch and smallsize scallops, with a risk of a small loss of commercial-sized scallops. These results are consistent with selectivity studies in other trawl fisheries where square-mesh codends have demonstrated their superior performance to diamond-mesh codends in reducing by-catch and discard rates, particularly in prawn and some fish trawl fisheries (Broadhurst 2000;Ordines et al 2006). Demersal trawl-gear selectivity studies for scallops are limited because most other scallop fisheries operate dredging gear.…”
Section: Discussionsupporting
confidence: 79%
“…Given that the focus of the Queensland mesh trials was to reduce by-catch by using square mesh, alternative square-mesh sizes were not tested; however, our study showed that largersized square-mesh codends than those tested in Queensland have the potential to concurrently reduce by-catch and smallsize scallops, with a risk of a small loss of commercial-sized scallops. These results are consistent with selectivity studies in other trawl fisheries where square-mesh codends have demonstrated their superior performance to diamond-mesh codends in reducing by-catch and discard rates, particularly in prawn and some fish trawl fisheries (Broadhurst 2000;Ordines et al 2006). Demersal trawl-gear selectivity studies for scallops are limited because most other scallop fisheries operate dredging gear.…”
Section: Discussionsupporting
confidence: 79%
“…Whereas, data from the BTF was available from previous studies (e.g., Ordines et al, 2006;Palmer et al, 2009;Quetglas et al, 2013), fishing tactics (a combination of target species, gear, and fishing location at a given time of the year; Pelletier and Ferraris, 2000), and fishery statistics from the SSF were determined within Myfish (for methodology, see Quetglas et al, 2016).…”
Section: Fisheries Descriptionmentioning
confidence: 99%
“…In the study area, commercial trawlers use up to four different fishing tactics (Palmer et al, 2009), which are associated with the shallow and deep continental shelf, and the upper and middle continental slope Ordines et al, 2006). Vessels mainly target striped red mullet (Mullus surmuletus) and European hake (Merluccius merluccius) on the shallow and deep shelf respectively.…”
Section: Fisheries Descriptionmentioning
confidence: 99%
“…Improving selectivity, in particular reducing catches of the smallest individuals, results in medium to long term higher yields per unit of fishing effort and in greater catch values (Broadhurst et al, 1996;Fonseca et al, 2005a,b). However, economic performance improvements may not be so straight forward in multi-species fisheries, such as the Mediterranean fisheries (Ordines et al, 2006;Tosunoğlu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%